The layered crystal structure of bis(theophyllinium) hexachloridostannate (IV), C14H18N8O8SnCl6 - Reiss Guido J.; Wyshusek Maik (Zeitschrift für Kristallographie - New Crystal Structures)
C14H18N8O8SnCl6, monoclinic, P21/n (no. 14), a = 8.1810(2) Å, b = 12.6195(3) Å, c = 11.3811(2) Å, β = 90.258(2)°, Z = 2, V = 1174.97(5) Å3, Rgt(F) = 0.0266, wRref = 0.0620, T = 290 K.